Moonlighting, Harm? : Student Perception of the Effect of Moonligthing, Achievement Motivation on Lecturer Performance - Hartina Fattah; Andi Batari Citta (Ilomata International Journal of Management, 2020)
This study aims to determine students 'perceptions of the term moonlighting lecturers and find out the effect of moonlinghting on lecturers' performance which is mediated by achievement motivation. This study uses quantitative methods with path analysis based on data from 145 student respondents in private universities in Jeneponto Regency. The results of the study showed that students perceive moonlighting as a natural thing for lecturers to do as an alternative to meet the needs of lecturers. The findings indicate that moonlighting has a significant positive indirect effect which is mediated by the achievement motivation of lecturers on the performance of